Voltage‐Control of Magnetism in All‐Solid‐State and Solid/Liquid Magnetoelectric Composites. Issue 26 (20th February 2019) - Molinari, Alan; Hahn, Horst; Kruk, Robert
Abstract: The control of magnetism by means of low‐power electric fields, rather than dissipative flowing currents, has the potential to revolutionize conventional methods of data storage and processing, sensing, and actuation. A promising strategy relies on the utilization of magnetoelectric composites to finely tune the interplay between electric and magnetic degrees of freedom at the interface of two functional materials. Albeit early works predominantly focused on the magnetoelectric coupling at solid/solid interfaces; however, recently there has been an increased interest related to the opportunities offered by liquid‐gating techniques. Here, a comparative overview on voltage control of magnetism in all‐solid‐state and solid/liquid composites is presented within the context of the principal coupling mediators, i.e., strain, charge carrier doping, and ionic intercalation. Further, an exhaustive and critical discussion is carried out, concerning the suitability of using the common definition of coupling coefficient α C = Δ M Δ E   to compare the strength of the interaction between electricity and magnetism among different magnetoelectric systems. Abstract : The magnetoelectric effect originates from the coupling between electric and magnetic degrees of freedom in matter. It can be realized at solid/solid and solid/liquid interfaces via strain, charge carrier doping, or ionic intercalation upon application of an external voltage.